(untitled) (American & British Studies Annual, 2017)
Michael Chabon’s second novel Wonder Boys (1995) focuses on Grady Tripp, a professor of creative writing whose personal and professional problems culminate during a writers’ festival on campus. A first person account of a series of unexpected events that Grady and his student James Leer experience in and outside of Pittsburgh during one weekend, the novel received mixed reviews. Whereas Robert Ward praised the text for being “the ultimate writing-program novel,” Michael Gorra denounced it, in a rather simplified way, as “another novel about a writer messing up his life.” Most famously, Jonathan Yardley in The Washington Post review appreciated the novel’s style and effective use of comic elements, but concluded that the text portrays a limited experience similar to the author’s own, thus urging Chabon “to move on, to break away from the first person and explore larger worlds.” While Chabon later seemed to follow Yardley’s advice in The Amazing Adventures of Kavalier and Clay (2000), an ambitious historical novel which earned him the Pulitzer Prize, this paper aims to reconsider Wonder Boys by drawing on its previous criticism and analyzing it as an amalgam of the campus novel, the picaresque as well as both Grady’s and James’s Bildungsroman.